PENGARUH PEMBERIAN HORMON 17β-ESTRADIOL TERHADAP PERKEMBANGAN GONAD SIPUT GONGGONG Laevistrombus turturella - Muzahar; Muhammad Zairin Jr.; Fredinan Yulianda; Muhammad Agus Suprayudi; Alimuddin; Irzal Effendi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
Dog conch Laevistrombus turturella is captured intensively, therefore, their population is decline. The dog conch culture is needed to maintain their population. The technology towards conch reproduction is still not developed yet in Indonesia. The 17β-estradiol hormone in conch and some mollusks has been stated by some researcher yet its main role in conch reproduction process has not widely known. The study about the addition of 17β-estradiol hormone in accelerating gonad development has never been reported. The aim of this study was to evaluate the impact of the addition of 17β-estradiol against dog conch’s gonad development. This study used three treatments for three groups of dog conch those were without injection (P1), injection by 30 µL of corn oil mixed with absolute ethanol (P2), and 30 µL of 17β-estradiol stock solution (P3). After injection, the dog conch was reared in pens culture in their natural habitat for 30 days. This study showed that the injection of a 17β-estradiol solution (P3) stimulated the dog conch’s gonad development as evidenced by greater oocyte mean diameter than another treatment. The mean of gonadal weight and GSI on P3 treatment was also higher than treatments P1 and P2. SDS-PAGE analysis showed that dog conch’s hemolymph has several kinds of proteins with varying molecular weights. Proteins with a molecular weight of 54-55 kDa are predicted as dog conch’s vitellogenin.